ANALISIS QUALITY CONTROL PEMERIKSAAN ERITROSIT,LEUKOSIT, DAN TROMBOSIT MENGGUNAKAN WESTGARD RULES DAN SIX SIGMA - Salsabilla Rizaldy; Tri Dyah Astuti; Woro Ummi Ratih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Quality control is part of a laboratory’s internal quality assurance program, which is conducted to monitor and maintain the accuracy and consistency of test results. Quality evaluation can be performed using the westgard rules and six sigma to assess the stability of analytical processes and the capability of testing methods. The westgard rules are used to detect random and systematic errors through the interpretation of control results, while six sigma is used to assess the capability of analytical processes based on precision, accuracy, and TEa, as well as to provide an estimate of the probability of errors occurring in one million tests. This study aims to evaluate the results of the westgard rules and six sigma analysis of erythrocyte, leukocyte, and platelet tests at the X Hospital Laboratory in Yogyakarta. This quantitative descriptive study with a cross-sectional approach used secondary data consisting of 55 quality control data points for low- and normal-level control materials from September to November 2025. The variables studied included the westgard rules and six sigma. Data were collected from quality control records and analysed using calculations of the mean, standard deviation, coefficient of variation, bias, westgard rules, and six sigma. The results of the study showed that erythrocytes violated rule 12s. Leukocytes violated rules 12s, 13s, 22s, 41s, and 10x, while platelets violated rules 10x, 12s, 13s, 22s, and 41s. The six sigma analysis results showed a low-level sigma value of 3.51 for red blood cells (moderate category) and a normal-level sigma value of 4.31 (good category); for white blood cells, a low-level sigma value of 3.65 (moderate category) and a normal-level sigma value of 5.00 (very good category); and a low platelet level of 2.33 (poor category) and a normal level of 4.43 (good category). The quality of erythrocyte and leukocyte testing is classified as good, while platelet testing still requires improved quality control to maintain the stability of the analytical process.